Cultural Rights of Traditional Musicians in Ethiopia: Threats and Challenges of Globalisation of Music Culture - Pati, R.N.; Yousuf, Shaik B.; Kiros, Abebaw (International Journal of Social Sciences and Management, 2015)
Ethiopia upholds unique cultural heritage and diverse music history in entire African continent. The traditional music heritage of Ethiopia has been globally recognized with its distinct music culture and symbolic manifestation. The traditional songs and music of the country revolves around core chord of their life and culture. The modern music of Ethiopia has been blended with combination of elements from traditional Ethiopian music and western music which has created a new trend in the music world. The music tradition of the country not only maintains the cultural identity but also maintains social cohesion through cultural expression at different social occasions and resists cultural changes infused through globalization. The globalization has brought a series of transformation and changes in the world of Ethiopian music through commercialization, commodification and digitalization of cultural expressions apart from hijacking the cultural rights of traditional musicians. The younger generations have been attracted towards western music undermining the aesthetic and cultural value of music tradition of the country. The international enactments relating to protection and safeguarding of cultural rights of people are yet to be appropriately translated into reality. The emergence of culture industries and entertainment houses has posed serious threats to local culture and led to disappearance of local traditions, musical heritage and their replacement by popular global music. The cultural homogeneity and commodification has replaced the multiplicity of cultures in this globalized era. This paper based on review of published articles and content analysis critically unfolds sensitive areas of cultural shock and violation of cultural rights exposed to traditional musicians and traditional singers of Ethiopia during last couple of decades. Int. J. Soc. Sci. Manage. Vol-2, issue-4: 315-326